DETEKSI SIMULTAN CMV DAN CHIVMV PENYEBAB PENYAKIT MOSAIK PADA TANAMAN CABAI DENGAN DUPLEX RT-PCR - Chandra, I Gede Agus Adi; Nyana, I Dewa Nyoman; Wirya, I G N Alit Susanta; Suastika, Gede (Journal of Agricultural Science and Biotechnology; Vol 5 No 1 (2016), 2016)
Detect the presence virus causes mosaic symptoms by CMV and ChiVMV infecting chili pepper plants at the same time was conducted. There needs a study that aims to detect the associations of both viruses causes mosaic symptoms by single or double infection and simplify the detection process which is necessary for a long and expensive process. The used method is a duplex RT-PCR in hopes of simultaneously detecting two viruses causes mosaic disease. Based on the results of the study showed that the duplex RT-PCR method can detect double infection of CMV and ChiVMV on chili plants and this method more effective to detect two viruses simultaneously in a single PCR reaction.
Keywords: chili pepper; CMV; ChiVMV; Duplex RT-PCR